Progress in environmental engineering water, wastewater treatment and environmental protection issues - Tomaszek, Janusz; Koszelnik, Piotr (CRC Press, 2015)
Progress in Environmental Engineering contains theoretical and experimental contributions on water purification, new concepts and methods of wastewater treatment, and ecological problems in freshwater ecosystems.